Psychological Model of Development of Professional Axiological Orientations in Prospective Teachers at the Stage of Higher Education - Vasilyevna Kudashkina, Olga; Victorovna Savinova, Tatyana; Alexandrovna Vdovina, Natalia; ., . (International Journal of Engineering and Technology, 2018)
The article defines the relevance of developing professional axiological orientations in prospective teachers and reviews the main research ideas on the topic. The aim of the article was to create a psychological model of development of professional axiological orientations of prospective teachers at the stage of higher education. The main methods of the study included theoretical analysis of the research literature on the topic of teachersâ€™ axiological orientations, as well as the method modelling that included the creation of the model of development of professional axiological orientations of prospective teachers at the stage of higher education. The authors presented the model that included the following inter-connected blocks: developmental, processing and resulting blocks. The developmental block includes the content, psychological-pedagogic conditions and mechanisms of the prospective teachersâ€™ professional axiological orientations development. The processing block defines the stages of the development. The resulting block includes the criteria and levels of the development. The content of the article reveals an opportunity for setting new goals in conducting professional axiological development of prospective teachers. Reaching these goals by integrating the international and national experience would help to efficiently organize the educational and mentoring process at the stage of higher education, which defines the future perspective of the study. Â Â Â